Pandemic Responsive Spaces for Local Economic Activities in the Old Town of Semarang (International Journal of Built Environment and Sustainability, 2022)
The COVID-19 pandemic has changed all aspects of life and order. It has made the Old Town of Semarang experience a decrease in the number of visitors. When the economy is starting and recovering, the pandemic sensitivity space is exercised through strict health protocol. This paper uses direct observation to examine the pandemic responsive space for local economic activities in the Old Town of Semarang. The following procedures were adopted for this study: 1) Defining the potential economic activity space in the Old Town of Semarang; 2) Recognising the presence of pandemic responsive space in location;  3) Analysing the responsive space in relation to pandemic context, and 4) Proposing space pattern that responsive to pandemic context. The study’s results are the Old Town of Semarang has three typologies of economic activity spaces, including cafes, restaurants, and street vendors. The economic activity in the form of cafes and restaurants has organised a responsive space to implement the established health protocols. In contrast, street vendors create unresponsive space for economic activity. This is because the street vendors have not been able to provide adequate supporting facilities for health protocols. Therefore, the local government and economic actors need to speed up the process for determining more pandemic responsive urban space that will allow economic activities to be carried out with proper health protocols
Keywords: COVID-19, pandemic, responsive space, economic activity, heritage sites, old town